Assessing the attitudes of medical students in their fourth year of study towards psychiatry and mental illness - Ochse, Stacey Leigh (My University, 2021)
Background: Existing researchrevealeda high prevalence of negative attitudes towards psychiatry and mental illness amongst medical students preceding formal psychiatric education. Anti-stigma interventions aimed at the level of medical students have beenpostulated to be most efficacious in reducing the risk of negative attitudes, which may drive stigmatisation and confer risk for poor medical care of psychiatric patients and reduced recruitment of junior doctors into psychiatry training posts. Aim: This study aimed to determine the prevalence of negative attitudes towards psychiatry and mental illness in a sample population of fourth-year medical students prior to formal psychiatric teaching. It also sought to ascertain whether other sociodemographic factors had bearing on their attitudes in this regard. Setting: The University of the Witwatersrand fourth-year medical student class of 2019. Methods: A cross-sectional, quantitative, descriptive study was conducted using the Mental Illness: Clinicians’ Attitudes Scale 2questionnaire (a validated scale for assessing negative attitudes of medical students towards psychiatry and mental illness) and a socio-demographic questionnaire. Results: Of the total scores, 97.2% fell below the median potential score of 56, reflecting a low prevalence of stigmatising attitudes. The African cohortexpressed less interest in psychiatry (80%), compared to other race cohorts (ranging from 92.1% to 100%). Conclusion: This study revealed a low prevalence of negative and stigmatising attitudes towards psychiatry and mental illness. Of statistical significance, was a relative difference in attitudes towards psychiatry and mental illness in different race cohorts (p=0.0017), however all race cohorts showed a low prevalence of negative and stigmatising attitudes towards psychiatry.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg in fulfilment for the requirements of the degree of Master of Medicine (Psychiatry)